Benchmarking Water Retail Cost Efficiency in England and Wales. Issue 3 (1st September 2020) - Williams, Sam; Pickard, Christopher; Glass, Karli; Glass, Anthony
Abstract: Privatised water companies in England and Wales are subject to economic regulation by the industry regulator (Ofwat). Ofwat sets 5-year caps on the prices' companies can charge their customers. These caps are in part based on the benchmarking of companies' costs. Ofwat has not previously used econometrics to benchmark domestic retail costs, but it undertook such modelling in its 2019 price review analysis. This is the first journal article to present an efficiency analysis of domestic water retail costs in England and Wales. Our approach is different from Ofwat's, as we propose two new ways of accounting for differences in the effect on cost of the number of single and dual service customers (water/sewerage-only and water and sewerage). Some companies' cost efficiencies vary greatly between the two ways. Depending on the approach to price capping, this could possibly have non-negligible implications for companies' caps.